Fecal microbiome transplantation attenuates manganese-induced neurotoxicity through regulation of the apelin signaling pathway by inhibition of autophagy in mouse brain - Jingjing Liu; Xin Zhang; Xiaojuan Ta; Miaomiao Luo; Xuhong Chang; Hui Wang (Ecotoxicology and Environmental Safety, 2022)
Manganese (Mn) is a common environmental pollutant. Mn exposure can lead to neurodegenerative diseases resembling Parkinson's disease, and has become a major public health concern. However, the mechanism of Mn-induced neurotoxicity in the brain is not clear. Fecal microbiome transplantation (FMT) may alleviate the neurotoxicity of Mn exposure by remodeling the gut microbiota. In this study, MnCl2 (manganese chloride) was administered to mice as in drinking water (Mn: 200 mg/L), and fecal matter from donor mice was administered by oral gavage every other day to the recipient mice. The Mn exposure model (Mn group) and FMT model (Mn+FMT group) were established and analyzed 5 weeks post-exposure. The Wipi1 gene exhibited the most significant increase associated with Mn exposure and Mn+FMT treatment groups based on transcriptome analysis. Combined analysis of transcriptomics and proteomics demonstrated that the apelin signaling pathway is the main pathway affected by FMT during Mn exposure. Immunofluorescence and Western blot showed that the expression of key proteins (Beclin-1, LC-3B, and PINK1) associated with autophagy in the hippocampus was robustly activated in the Mn exposure group, but attenuation was observed in Mn+FMT mice, suggesting a critical role of autophagy in neurotoxicity induced by Mn exposure. Our research provides evidence for the neurotoxic effects of Mn exposure through autophagy activation and provides an underlying mechanism of FMT protection against Mn-induced neurotoxicity through regulation of the apelin signaling pathway.